Study of Blind Hole Drilling in Inconel 718 Using Cryo-Treated Cu Tool Electrode Assisted EDM - Manas Kumar, Rakesh Kumar, Satish Namdev (International Journal of Advanced Science and Technology, 2020)
In this paper, analysis of machining performance for Inconoly 718 work-piece material with cryo-treated Cu-tool electrode via Taguchi approach is conveyed. Investigational study is conducted using rotary electrical discharge drilling fabricated setup to investigate the impact of machining factors like tool diameter (dt), discharge current (Ip), pulse-on time (tON), pulse-off time (tOFF), tool rotation (Nt) and hole depth (h) on Metal Removal Rate (MRR). Investigation using Taguchi method reveals that, at 95 % confidence level, dt, Ip & tON are substantial factors affecting MRR. An optimum combination has been found for maximum MRR by using Taguchi’s response table. A mathematical model has been developed for computing MRR at optimum level. The maximum MRR was found 13.615 mm3/min in present study.